2010
DOI: 10.1038/leu.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B cell leukemia with highly specific allogeneic T cells with a public recognition motif

Abstract: The possibility that allogeneic T cells may be targeted to leukemia has important therapeutic implications. As most tumor antigens represent self-proteins, high-avidity tumor-specific T cells are largely deleted from the repertoire of the patient. In contrast, T cells from major histocompatibility complex (MHC)-mismatched donors provide naïve repertoires wherein such cells have not been systematically eliminated. Yet, evidence for peptide degeneracy or poly-specificity warrants caution in the use of foreign hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…The concept that cancer cells can be targeted by T cells recognizing self-peptides presented by foreign HLA was first described by Stauss and coworkers (15)(16)(17). Although these and other studies have shown that certain peptides can be specifically recognized when presented on allogeneic HLA (8,9,12,(18)(19)(20)(21)(22)(23), it seemed possible that they represented exceptions, because there is also evidence that allorestricted cells are more promiscuous with regard to peptide recognition (9,18,(24)(25)(26)(27)(28). However, when assessing reactivity to a large number of epitopes at the single-cell level, we did not find evidence suggesting that peptide recognition on foreign HLA generally has a low specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept that cancer cells can be targeted by T cells recognizing self-peptides presented by foreign HLA was first described by Stauss and coworkers (15)(16)(17). Although these and other studies have shown that certain peptides can be specifically recognized when presented on allogeneic HLA (8,9,12,(18)(19)(20)(21)(22)(23), it seemed possible that they represented exceptions, because there is also evidence that allorestricted cells are more promiscuous with regard to peptide recognition (9,18,(24)(25)(26)(27)(28). However, when assessing reactivity to a large number of epitopes at the single-cell level, we did not find evidence suggesting that peptide recognition on foreign HLA generally has a low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional T-cell responses were measured as mobilization of CD107a/b (degranulation) and production of IFN-γ by flow cytometry, as described in ref. 23, following coculture with various target cells that were DNA-transfected 48 h earlier, mRNA-transfected 4-10 h earlier, or peptideloaded at 10 μM or indicated concentration for 4-12 h. CD4 pos T cells were isolated using a CD4-positive isolation kit (Dynal Biotech), whereas monocytes were isolated by elutriation centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Self-reactive T cells can be difficult to identify in the autologous T cell repertoire. 43 Moreover, allo-reactive TCRs can readily be obtained that react to self-antigens with superior affinity relative to those identified in an autologous setting. 44,45 Strong binding of re-directed T cells to the intended target is important for clinical efficacy, 11,46 but on-target and off-target binding to cells other than the intended can potentially cause hazardous toxicities, 31,[47][48][49][50][51] and reviewed in 15 .…”
Section: Cd8mentioning
confidence: 99%
“…40 In addition, antigen-specific T cells were obtained by stimulating T cells from HLA-A2-negative donors with autologous dendritic cells (DCs) pulsed with RNA to express HLA-A2 in parallel with a variety of targeted antigens. [41][42][43] In this study, from HLA-A*0201/B*0702-negative healthy individuals, we isolated 3 T-cell clones targeting 3 distinct CD79b peptides presented in HLA-A*0201 or HLA-B*0702. CD79b-positive primary CLL, ALL, and ALL cell lines were recognized by these T-cell clones, whereas no reactivity toward nonhematopoietic tissue was detected.…”
Section: Introductionmentioning
confidence: 99%